A novel B*07 variant allele, B*07:416, identified by next‐generation sequencing. (4th March 2021) - Tang, Mei San; Duffy, Brian F.; Jennemann, Jo‐Ellen; Parikh, Bijal A.; Liu, Chang
Abstract : HLA‐B*07:416 differs from HLA‐B*07:02 by a missense mutation at codon 92 of the cDNA sequence.